2020
DOI: 10.1101/2020.05.14.095828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid endo-lysosomal proteins as potential biomarkers for Huntington’s disease

Abstract: 25Molecular markers derived from cerebrospinal fluid (CSF) represent an accessible 26 means of exploring the pathobiology of Huntington's disease (HD) in vivo. The endo-27 lysosomal/autophagy system is dysfunctional in HD, potentially contributing to 28 disease pathogenesis and representing a potential target for therapeutic intervention. 29Several endo-lysosomal proteins have shown promise as biomarkers in other 30 neurodegenerative diseases; however, they have yet to be fully explored in HD. We 31 performed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…We pooled plasma NfL measurement data from the Kids‐HD/JHD with adult participants from HD‐CSF 6,8,12 to evaluate the nonlinear plasma NfL dynamics by disease burden score (DBS = age × [CAG‐35.5]) 14 using LMER models. A two degrees‐of‐freedom test was performed for the joint significance of the two‐spline transformation of DBS.…”
Section: Methodsmentioning
confidence: 99%
“…We pooled plasma NfL measurement data from the Kids‐HD/JHD with adult participants from HD‐CSF 6,8,12 to evaluate the nonlinear plasma NfL dynamics by disease burden score (DBS = age × [CAG‐35.5]) 14 using LMER models. A two degrees‐of‐freedom test was performed for the joint significance of the two‐spline transformation of DBS.…”
Section: Methodsmentioning
confidence: 99%
“…This reinforces the specific role of neuroinflamation in AD but not in other neurodegenerative diseases. In addition, this result contributes to clarify ongoing controversies on the role of beta‐amyloid deposition in early PD and HD 20–25 …”
Section: Discussionmentioning
confidence: 82%
“…In addition, this result contributes to clarify ongoing controversies on the role of beta-amyloid deposition in early PD and HD. [20][21][22][23][24][25] F I G U R E 2 Schematic representation of the biological interpretation of intracortical mean diffusivity (MD) changes. In normal conditions, the diffusion of water (blue lines) within the cerebral cortex is restricted by local neuronal density (purple cells).…”
Section: Neuroimaging Study Clinical Context Added Value Of Surface-b...mentioning
confidence: 99%
“…A recent study demonstrated an association between lower levels of CSF amyloid precursor protein (APP) and worse clinical phenotype and lower cognitive performance in HD patients [52], the strongest relationship observed with composite UHDRS score. APP is a transmembrane protein with multiple physiological functions, including regulating brain iron homeostasis [53], and it is cleaved by beta- and gamma-secretase to form Aβ peptides [54, 55].…”
Section: Discussionmentioning
confidence: 99%